Collaborative Discussion Using Padlet-based Materials in Writing for ESP Course - Fauzul Etfita; Sri Wahyuni (STAI Hubbulwathan Duri, 2021)
Collaborative discussion is a purposeful means for lecturers to assist students’ ideas in writing. This research, therefore, aims to determine the effect of collaborative discussion using Padlet-based materials that have been previously developed by researchers for Mechanical Engineering students to enhance learning outcomes. This research was conducted at second-year undergraduate in a class of 40 students. This research was classified as a pre-experimental design. Moreover, the quantitative data were collected by using pre-test and post-test to the sample class. The finding revealed descriptive statistics of the sample studied, pre-test and post-test. For the pre-test value, an average learning outcome or mean of 60.13 is obtained. While for the post-test score, it was obtained the average value of learning outcomes of 77.25. Furthermore, the correlation coefficient or correlation is equal to 0.867 with a significance value (Sig.) of 0.000. The finding indicates that Collaborative learning using Padlet-based teaching materials in Mechanical Engineering class could influence students’ writing outcomes.